Ethnobotanical Study Ethnobotanical Study and Phytochemical Review of Medicinal Plants Used by the Pandalungan Community in Taman Village, Bondowoso, Indonesia: An Insight into Traditional Knowledge and Bioactive Potential for Sustainable Utilization - Nia, Imaniah Bazlina Wardani; Adzkafillah Nuruzzaman; Risma Nurlim; Nanda Eska Anugrah Nasution; Wahyu Anggar Wanto (Jurusan Biologi Universitas Negeri Makassar, 2025)
Indonesia, as a megadiverse country, holds extensive biodiversity and rich local knowledge, particularly in the use of medicinal plants. This study aimed to document the use of traditional medicinal plants by the Pandalungan community in Taman Village, Grujugan District, Bondowoso Regency, and to assess their phytochemical potential. A qualitative approach was employed through semi-structured interviews using purposive and snowball sampling. Data was collected covering plant species, parts used, and sources of acquisition. A literature-based phytochemical review was also conducted to evaluate the scientific potential of the identified species. The Use Value (UV) was calculated to determine the cultural importance of each species. A total of 25 medicinal plant species were documented, with 13 cultivated, 5 wild, and 7 sourced from traditional markets. The highest UV scores were recorded for Zingiber officinale, Piper betle, Moringa oleifera, and Syzygium polyanthum. Literature analysis revealed that these plants contain key phytochemicals such as flavonoids, alkaloids, saponins, tannins, terpenoids, phenols, and essential oils. The findings indicate that local ethnobotanical knowledge holds significant potential for developing natural remedies based on local biodiversity, reinforcing the need for further research and conservation efforts.